Myrmicella, a new genus of Harpactorinae (Hemiptera: Heteroptera: Reduviidae) from Madagascar - Chłond, Dominik; Baňař, Petr (Zootaxa, 2013)
Myrmicella verticospinosa gen. et sp. nov., is described, based on four specimens (two males and two females) collected in south-west Madagascar (Zombitse-Vohibasia National Park and Isalo National Park). Three specimens have been collected by sifting the leaf litter, one female was collected using yellow pan traps. Genitalia of both sexes are described and illustrated.